Experimental study of performance and QoS of multicast and unicast video traffic in WAN links - Facchini, Higinio Alberto (2017)
In recent years there has been an exponential increase in the growth in multimedia applications, and in particular in video applications. In this work, a quantitative analysis is performed by experimentation, in order to evaluate the behavior and impact of video traffic on WAN networks. We propose a WAN test bed with four scenarios that allows to inject unicast or multicast video traffic, compressed with several codecs. From capturing video traffic, we identified several interesting performance and QoS metrics. We include detailed contributions on the impact produced by several factors, when there are restrictions on the bandwidth, as in a corporate real WAN link of some few Mbps. The work oriented on the configurations to be taken into account for an adequate management of similar networks and an efficient use of the resources available, without compromising the performance and the expected QoS.